2020
DOI: 10.3390/biom10010075
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants in IL-20 Gene are Associated with Subclinical Atherosclerosis, Cardiovascular Risk Factors and IL-20 Levels in the Cohort of the Genetics of Atherosclerotic Disease (GEA) Mexican Study

Abstract: Inflammation has been involved in the development of atherosclerosis, type 2 diabetes mellitus, insulin resistance, and obesity. Interleukin 20 is a pro-inflammatory cytokine encoded by a polymorphic gene located in chromosome 1. The aim of the study was to evaluate the association of two IL-20 polymorphisms (rs1400986 and rs1518108) with subclinical atherosclerosis (SA), cardiovascular risk factors and IL-20 levels in a cohort of Mexican individuals. The polymorphisms were determined in 274 individuals with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Additionally, a case-controlled study demonstrated that serum levels of interleukin (IL)-6 were significantly higher in patients with ADHD than in healthy controls [ 31 ]. Chronic exposure to inflammation may be a risk factor for CVD by adversely affecting endothelial functions through proinflammatory cytokine, causing subclinical AS [ 32 , 33 ]. In addition, in a meta-analysis, chronic inflammation was found inde-pendently associated with higher IMT levels [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a case-controlled study demonstrated that serum levels of interleukin (IL)-6 were significantly higher in patients with ADHD than in healthy controls [ 31 ]. Chronic exposure to inflammation may be a risk factor for CVD by adversely affecting endothelial functions through proinflammatory cytokine, causing subclinical AS [ 32 , 33 ]. In addition, in a meta-analysis, chronic inflammation was found inde-pendently associated with higher IMT levels [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another pro-inflammatory cytokine with an atherogenic effect that causes microvascular lesions due to the induction of angiogenesis in hypoxic tissue is IL-20. In AMI, it promotes cardiomyocyte apoptosis and increases myocardial reperfusion injury [18,19]. In addition, there is evidence that cardiomyocyte necrosis in ischemic myocardium contributes to the release of pro-inflammatory cytokines and hsCRP [20].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a case–control study nested in the Genetics of Atherosclerotic Disease (GEA) study. The GEA study is a prospective cohort that comprised adults with pCAD and healthy controls without a personal or family history of pCAD [ 27 ]. The main goal of this cohort was to elucidate the genetic factors associated with pCAD and other coronary risk factors in the Mexican population.…”
Section: Methodsmentioning
confidence: 99%